TERAPI DALAM ISLAM PERSPEKTIF HADIS - Aprahul Fhadilah Nasution; Abdul Halim (UIN Sumatera Utara Medan, 2025)
The growth of industrialization, modernization, and advancements in science and technology has impacted community lifestyles, making them increasingly complex. Modern individuals often experience alienation and loneliness caused by rapid social changes. Lifestyles have shifted from simplicity to luxury; meanwhile, uncontrolled career ambitions, materialism, and dissatisfaction with income can lead to stress. Such mental health issues can disrupt interpersonal relationships within both the family and society. To overcome these challenges and maintain mental well-being, disciplined mental guidance or education is required. This study aims to explore and identify mental health education from the perspective of the Prophet's Hadith, as well as to understand the implementation of SEFT (Spiritual Emotional Freedom Technique) and the Logos Institute programs in fostering a healthy mind. This research employs a descriptive qualitative approach, with data collection techniques including observation, interviews, and literature reviews. The results indicate that Prophet Muhammad (PBUH), through his Hadith, provided examples of mental cultivation through prayer (salat), supplication (dua), and remembrance (dhikr) performed with sincerity and focus (khusyu'), as well as through Sharia-compliant healing methods. The implementation of SEFT to maintain mental health through Logos programs includes SEFT Healing, Praying with Full Love (Salat Sepenuh Cinta), the Personal Peace Procedure, and Divine Love Initiation (DLI).